Disasters and life in anticipation of slow calamity - Staupe-Delgado, Reidar, author.
1 online resource (xiv, 137 pages)
Keywords: "The book provides insights into community narratives concerning life in the face of creeping calamities through a case study from the Colombian Andes. It sets out to make sense of the lived experience of disasters that are slowly unfolding as well disasters that have not yet occurred. The inter-disciplinary blend of practice-oriented and conceptual reflections will appeal to academics in postgraduate and postdoctoral research in social sciences, specifically, disaster research, geography, and research fields centred on natural hazards and disasters"--